Thromboelastometry analysis of severe North American pit viper-induced coagulopathy: A case report. (1st September 2018) - Cao, Dazhe; Domanski, Kristina; Hodgman, Erica; Cardenas, Carlos; Weinreich, Mark; Hutto, Jake; AbdelFattah, Kareem R.; Chen, Catherine
Abstract: Case details: A 51-year-old man presented with rapid onset encephalopathy and respiratory failure after a suspected intravascular envenomation from a North American pit viper. The patient received antivenom and was transferred to a tertiary care facility where he had cardiovascular collapse and persistent coagulopathy requiring 28 vials of Crotalidae polyvalent immune Fab antivenom for initial control and six vials for maintenance. The patient's coagulopathy was monitored using "traditional" measures (platelets, fibrinogen, and prothrombin time/international normalized ratio) and rotational thromboelastometry (ROTEM ® ). The patient also subsequently developed intestinal necrosis requiring exploratory laparotomy with ileum and colonic resections, and anuric renal failure requiring continuous renal replacement therapy. After coordinated multidisciplinary management, he was discharged to an acute inpatient rehabilitation on hospital day 25 and has since made a full recovery. Discussion: In the setting of a severe intravascular pit viper envenomation, thromboelastometry correlated well with "traditional" measures. During recovery, ROTEM ® demonstrated measurable improvements in the extrinsic coagulation pathway while the INR remained between 1.5 and 1.6. Patient's intestinal necrosis may have resulted from microvascular thrombosis due to Crotalinae venom. The patient's ultimate recovery necessitated a coordinated multidisciplinary effort. ROTEM ® abnormalities after North American pit viper envenomation may be more sensitive than "traditional" measures and may have prognostic value to determine the severity of envenomation, but further research to define its utility is required. Highlights: A severe North American pit viper envenomation resulted in cardiovascular collapse, intestinal necrosis, and renal failure. Use of rotational thromboelastometry (ROTEM ® ) correlates well with measurements of fibrinogen and prothrombin time/INR. EXTEM specification may be more sensitive than INR alone in evaluating extrinsic pathway abnormalities.